Does the Video Assistant Referee (VAR) technology mitigate referee bias in professional football leagues? - Chang Hyun Kim; Kyung Yul Lee; Young Sun Kwon (International Telecommunications Society (ITS), 2022)
Evidence for home advantage is clear in sports including professional football. Among the factors that lead to home advantage is referee bias where referees make biased decisions in favor of the home sides. In order to minimize any bias or unrighteousness caused by referee bias, the Video Assistant Referee (VAR) was introduced to the world of professional football and is now widely adopted in domestic leagues across the world. However, it was not until 2018 when professional football leagues started to implement the VAR with the Australian A-League being one of the first football leagues to adopt the technology. This study compares the effects of the VAR technology on home advantage using difference-in-difference model and synthetic control method with eight professional football leagues constructing the treatment group and other 45 leagues constructing the control group. With home advantage measured with the number of goal counts, it is found that the adoption of the VAR technology significantly increases the average number of away team goals while the average number of home team goals remains unchanged. These findings may help better understand the effects of the VAR on home advantage, and the fact that econometrics models were applied to understand it effects carries importance as well.
Keywords: 330